2020
DOI: 10.1177/1756284819896179
|View full text |Cite
|
Sign up to set email alerts
|

Redo endoscopic sleeve gastroplasty: technical aspects and short-term outcomes

Abstract: Background: Endoscopic sleeve gastroplasty (ESG) is a restrictive endoscopic bariatric procedure providing promising results. In this short case series, we analyze the technical aspects and short-term outcomes of the redo ESG. Methods: A retrospective analysis was done on a prospective database of all patients that were selected by a multidisciplinary team that underwent ESG between March 2017 and May 2019. Patients that underwent a redo ESG because of a progressive loss of satiety, weight regain, or insuffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…The recent emergence of bariatric endoscopic techniques promises less invasive, more cost-effective, and repeatable [5] approaches to the treatment of obesity. Endoscopic sleeve gastroplasty (ESG) consists of tubularization of the gastric cavity created by placing full-thickness sutures in a triangle and in a top-to-bottom direction from the gastric angulus towards the gastric fundus, preserving the area of the pyloric antrum and a part of the fundus itself.…”
Section: Introductionmentioning
confidence: 99%
“…The recent emergence of bariatric endoscopic techniques promises less invasive, more cost-effective, and repeatable [5] approaches to the treatment of obesity. Endoscopic sleeve gastroplasty (ESG) consists of tubularization of the gastric cavity created by placing full-thickness sutures in a triangle and in a top-to-bottom direction from the gastric angulus towards the gastric fundus, preserving the area of the pyloric antrum and a part of the fundus itself.…”
Section: Introductionmentioning
confidence: 99%
“…No peri-procedure complications were reported after the redo procedure, and all four patients reported excellent satiety after this redo procedure. 86 Although this study had a small sample, it showed promising results for a redo procedure.…”
Section: Society Guidelinesmentioning
confidence: 90%
“…A maximum of 4 bites was used 7 to avoid too much stirring of the stomach, which could lead to too much pressure on the gastric wall and eventually to gastric perforation. Adding too much pressure between the sutures should also be avoided to reduce the pressure on the stomach.…”
Section: Description Of the Technique And Technical Aspectsmentioning
confidence: 99%
“…In case of failure of weight loss, redo ESG after primary ESG (both with Apollo Overstitch) has been proved to be safe and effective, with 100% of technical success and about 19% of total body weight loss within 1 year. 7,8 To our knowledge, ESG with Apollo Overstitch after failed POSE-2 procedure has not yet been described. Here, we describe the clinical results and technical aspects of the first case of ESG with Apollo Overstitch after a previous POSE-2 procedure.…”
Section: Introductionmentioning
confidence: 99%